Literature Analysis of Governance in Local Productive Arrangements. a Systematic Review - Correia Lima Franca, Adriana; Bezerra Alves, Christiane Luci; Domingues Waltenberg, Fábio (Geografares, 2024)
The study analyzes the quantity of scientific publications related to governance in Local Productive Arrangements (LPAs), the purpose is to identify the main approaches within this theme and to point out any research gaps. So, a Systematic Literature Review covering the last 20 years was conducted. The publications survey was conducted on the Portal of Journals of the Coordination for the Improvement of Higher Education Personnel (CAPES), Scientific Periodicals Electronic Library (SPELL), and Scientific Electronic Library Online (SCIELO), and 34 articles were cataloged. Among the main results, the importance of governance stands out, as it facilitates synergies, enabling the promotion of competitiveness and development of LPAs. The greatest challenges lie in the absence of practices of open and continuous negotiations and the limited emphasis given to environmental issues.